2017 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--28307
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Canvas-Based Online Homework for Engineering

Abstract: Arbor. His current interests include multi-functional composites, material modeling, and traditional mechanics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…Communication tools including web conferencing, video conferencing, and email listserv also are being utilized for the collaboration, which enable the Network statisticians to participate in bi-directional communication flow. As evidenced in the previous studies [ 22 , 23 ] which proved the significant effect of networking tool on the performance, this approach is expected to reduce the learning curve for various statistical techniques and increase the expertise within the network. In addition, the DCC plans to utilize the infrastructure to support biostatistical collaborations and communication across the network: eagle-i (Resource Discovery Networking system), RTRN website, and Profiles (Research Networking system).…”
Section: Strategic Approaches For Collaborationmentioning
confidence: 87%
“…Communication tools including web conferencing, video conferencing, and email listserv also are being utilized for the collaboration, which enable the Network statisticians to participate in bi-directional communication flow. As evidenced in the previous studies [ 22 , 23 ] which proved the significant effect of networking tool on the performance, this approach is expected to reduce the learning curve for various statistical techniques and increase the expertise within the network. In addition, the DCC plans to utilize the infrastructure to support biostatistical collaborations and communication across the network: eagle-i (Resource Discovery Networking system), RTRN website, and Profiles (Research Networking system).…”
Section: Strategic Approaches For Collaborationmentioning
confidence: 87%
“…In addition, VR labs will improve access to high-quality experiments for institutions lacking experimental capacity as well as for many students with physical disabilities. Students are increasingly required to use computer-based systems, such as Blackboard, Canvas and other learning management software (LMS) to complete course requirements and have demonstrated proficiency with computer-based homework and assignments [1]. However, utilizing VR experiments for traditional lab requirements with current generation VR hardware is relatively novel to both the faculty and the students.…”
Section: Department Of Mechanical and Energy Engineering Indiana University-purdue University Indianapolismentioning
confidence: 99%
“…Head and Owolabi [3] found that use of online homework in an engineering mechanics course improved student grades thus suggesting an enhancement of student learning. Jones [4] used the Canvas based online homework in an engineering materials course which resulted in higher scores on exams and a higher correlation between homework scores and exam scores; this finding was attributed to the immediate feedback on the correctness of the problem as well as allowing multiple attempts to solve the problem. Liberatore [5] used an online homework system that asks the same questions of each student while changing one or more numeric values in the problem statement, and observed statistically significant improvements in student achievement in material and energy balance topics.…”
Section: Introductionmentioning
confidence: 99%